Acid Resistance and Strength Performance of Bamboo Leaf Ash–Bone Ash Concrete under Simulated Acid Rain Conditions - Auwal , Abdullahi Umar (Journal of Building Materials and Structures, 2025)
Concrete infrastructure in oil and gas environments faces rapid degradation due to exposure to acid rain and chemically aggressive discharges. Conventional Ordinary Portland Cement (OPC) concrete is particularly vulnerable in such zones, necessitating the development of more durable and sustainable alternatives. This study investigates the use of Bamboo Leaf Ash (BLA) and Bone Ash (BA) as partial OPC replacements for enhancing concrete’s resistance to acid attack. A binary pozzolanic system was developed by replacing OPC with 5–30% BLA–BA blends while maintaining a fixed water-to-binder ratio. Concrete mixes were evaluated for slump, compressive strength (3–56 days), hardened density, and acid resistance through mass loss and residual strength after 28-day immersion in a simulated acid rain solution (1% H₂SO₄ + 1HNO₃). Statistical techniques including ANOVA, regression modeling, and Pearson correlation analysis were employed to analyze and predict performance trends. The optimum mix, containing 10% BLA + 5% BA, achieved a 28-day strength of 33.14 N/mm², residual strength retention of 97.59%, and the lowest mass loss (2.4%) under acid exposure. Regression models yielded R² values exceeding 0.84, indicating strong predictive reliability. Visual inspection confirmed reduced surface degradation compared to the control. These findings demonstrate that BLA–BA concrete offers superior acid durability and aligns with sustainability objectives through waste valorization and reduced cement demand. The proposed mix is particularly suitable for acid-prone infrastructure in refineries, petrochemical plants, and industrial wastewater systems.